(untitled) (Bangladesh Journal of Botany, 2025)
This study investigated the changes in soil water transport and nutrient content under plant-microbe synergistic remediation in a mining area. To restore and improve heavy metal contaminated soils, three enriched plant species were used in combination with microbial agents. Results showed that herbaceous plants significantly improved soil texture in the short term. The highest soil moisture was observed in the 0-20 cm layer, especially in the AH treatment (EM fungi + Vetiver grass + Seabuckthorn). AH also reduced soil pH most effectively. The AX treatment (EM fungi + Vetiver grass) increased soil organic matter by 25.7% compared to the control. Rhizobia combined with shrub grass planting enhanced soil nitrogen. Both AX and AH significantly increased effective phosphorus (57.1 and 55.6 mg/kg) and available potassium (194 and 174 mg/kg), as well as total microbial counts (4.071 × 107 and 3.561 × 107 cells/g), showing increases of 94.8 and 70.4%, respectively, over the control. Overall, AH and AX treatments were most effective in improving soil moisture and quality in contaminated mining areas. Bangladesh J. Bot. 54(3): 865-873, 2025 (September) Special